Muhammadiyah Māʻūnic Philosophy and Financial Inclusion: A Maqasid Perspective - Syamsul Anwar (IJISH (International Journal of Islamic Studies and Humanities), 2021)
Muhammadiyah’s al-Maun philosophy is a religious and social outlook developed by this organization, and underlies social programs, activities, and works it carries out in order to achieve an ideal form of human life organizing, i.e. what is called “a true Islamic society.” Inspired by the philosophical stance of existential dualism, while giving emphasis on the relative importance and significance of worldly life, this largest Muslim social association in Indonesia, in contradistinction to the the Sufis’ attitude, sees the world as a divine gift onto humankind and it is, therefore, good and innocent, as well as malleable and capable of recieving human conduct to construct it for the common benefits of humankind. This philosophy takes five principle as its bases: the doctrine of tawḥīd; the societal nature of human; the primacy of ethical values of justice, trustworthiness, fraternity, and solidarity; observance of divine law; and the importance of organization. Extracted out of sūrat al-Māʻūn in the Quran and hence its name, this philosophy aims to actualize the social dimension of maqāṣid al-sharīʻa, i.e. to realize the good interests of society’s members as a whole including, and primarily, the vernarable segment among them.